Distribution of heritage To People Which made lost (mafqud) According to Islamic Law - Anindita Atibhakti Ardhani (International Journal on Advanced Science, Education, and Religion, 2019)
The purpose of this study is to understand the division of inheritance against people who are declared missing (mafqud) according to Islamic law. The problems examined in this study concerning legal certainty for heirs who were declared missing (mafqud) in the right to inherit and distribution of inheritance after the person declared missing (mafqud) is known to exist. The research method used is normative legal research. The results of the study are the heirs who lost (mafqud) still have rights, be they rights to property or inheritance. This right remains attached as it is when it is still in normal life. When the heirs leave the residence for a considerable time, then their status becomes a lost person (mafqud), then their life status is still recognized. The mafqud heirs mentioned above are part of the heirs due to blood relations (caused by birth) based on the An-Nisa surah, especially verses 7 and 8. Furthermore, the inheritance case for the mafqud heirs whose existence is known, can still obtain the inheritance part even though the portion has been spent by other heirs, because in fact the heirs who were declared missing or the mafqud may have a substitute heir who will replace the position of the heirs declared mafqud when the inheritance is distributed to the heirs as stipulated in Article 185 verses (1) and (2) KHI.